How to ensure the sustainable supply of childcare educators: factors influencing student teachers’ career choice - Wang, Xinghua; Liu, Yi; Qiu, Yue; Tang, Jin; Wang, Dan; Zou, Jun (Frontiers in Education, 2024)
Guided by the Factors Influencing Teaching Choice ( FIT-Choice) model, this study investigates the career choices of student teachers majoring in childcare and analyses the factors influencing their career choices to address the teacher recruitment issue in the childcare industry in China. A total of 444 participants from vocational colleges were selected, and questionnaires were used to ask about their career choice intention and the influencing factors. The results showed that the FIT-Choice model is theoretically acceptable, although the subscales for personal utility value should be reformulated. Students majoring in childcare have a positive but weak intention to become childcare educators. Their career choice intentions are jointly influenced by their social influences, task perceptions, values and fallback career, with task perceptions and values playing mediating roles between social influences and career choice intentions.